2020
DOI: 10.3390/nu12103152
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Literacy and Nutritional Status Assessment with Glycemic Control in Adults with Type 2 Diabetes Mellitus

Abstract: While the role of medical and nutrition factors on glycemic control among adults with type 2 diabetes mellitus (T2DM) has been well-established, the association between health literacy (H.L.) and glycemic control is inconsistent. This study aims to determine the association of H.L. and nutritional status assessments with glycemic control in adults with type 2 diabetes mellitus. A total of 280 T2DM respondents (mean (SD) age = 49.7 (10.3) years, Glycated hemoglobin (HbA1c) = 9.9 (2.6) %, and Body Mass Index = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
3
20
0
3
Order By: Relevance
“…This finding is in line with the study by Papp-Zipernovszky et al (2016), which was the first research in Hungary that compared the scores of individuals with chronic illness to those of a healthy population and found that chronic patients had significantly lower FHL levels. Related studies by Agad Hashim et al (2020), Abdullah et al (2019) and Van der Heide et al (2014) also support the aforementioned result in which the presence of type 2 diabetes is in association with the individuals' FHL levels [35,58,59]. In addition, the results of the present study are consistent with the data of Cavanaugh et al (2011), in which lower FHL levels among diabetes patients were between 15 and 40%, depending on the sample.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the study by Papp-Zipernovszky et al (2016), which was the first research in Hungary that compared the scores of individuals with chronic illness to those of a healthy population and found that chronic patients had significantly lower FHL levels. Related studies by Agad Hashim et al (2020), Abdullah et al (2019) and Van der Heide et al (2014) also support the aforementioned result in which the presence of type 2 diabetes is in association with the individuals' FHL levels [35,58,59]. In addition, the results of the present study are consistent with the data of Cavanaugh et al (2011), in which lower FHL levels among diabetes patients were between 15 and 40%, depending on the sample.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the study by , which was the first research in Hungary that compared the scores of individuals with chronic illness to those of a healthy population and found that chronic patients had significantly lower FHL levels. Related studies by Agad Hashim et al (2020), and also support the aforementioned result in which the presence of type 2 diabetes is in association with the individuals' FHL levels [35,58,59]. In addition, the results of the present study are consistent with the data of , in which lower FHL levels among diabetes patients were between 15 and 40%, depending on the sample.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in a study examining the effect of health literacy and nutritional status on the glycemic values of individuals with diabetes, it was found that there was a negative correlation between glycemic values and BMI and the level of nutritional knowledge. 30 In this study, it was observed that inadequate/limited nutritional literacy negatively affected the metabolic control values and quality of life. Accordingly, a range of educational policies should be developed to increase the nutritional literacy levels of individuals with diabetes.…”
Section: Discussionmentioning
confidence: 79%